2018
DOI: 10.3389/fpls.2018.00940
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a SDD1-Like Gene From Wild Tomato Decreases Stomatal Density and Enhances Dehydration Avoidance in Arabidopsis and Cultivated Tomato

Abstract: Stomata are microscopic valves formed by two guard cells flanking a pore, which are located on the epidermis of most aerial plant organs and are used for water and gas exchange between the plant and the atmosphere. The number, size and distribution of stomata are set during development in response to changing environmental conditions, allowing plants to minimize the impact of a stressful environment. In Arabidopsis, STOMATAL DENSITY AND DISTRIBUTION 1 (AtSDD1) negatively regulates stomatal density and optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 98 publications
(121 reference statements)
2
31
0
Order By: Relevance
“…Transcripts were detected in meristemoids (stomatal initials) and GMCs, but were absent in mature stomata indicating a developmental rather than a constitutive role of SSD1 in stomatal formation [35]. In agreement to these results, Morales-Navarro et al [36] reported increased transcription of the gene in growing tomato leaves suggesting the involvement of SDD1 in their development. SDD1 is a negative regulator of stomatal development, since it lessens both the formation of stomatal complexes and the number of stomata produced per stomatal complex [34].…”
Section: Subtilisin-like Serine Proteasessupporting
confidence: 56%
See 2 more Smart Citations
“…Transcripts were detected in meristemoids (stomatal initials) and GMCs, but were absent in mature stomata indicating a developmental rather than a constitutive role of SSD1 in stomatal formation [35]. In agreement to these results, Morales-Navarro et al [36] reported increased transcription of the gene in growing tomato leaves suggesting the involvement of SDD1 in their development. SDD1 is a negative regulator of stomatal development, since it lessens both the formation of stomatal complexes and the number of stomata produced per stomatal complex [34].…”
Section: Subtilisin-like Serine Proteasessupporting
confidence: 56%
“…This contact between neighboring stomata has been related to pitfalls, including reduced carbon assimilation and impaired stomatal responses to external cues [22]. Moreover, similar functionality of SDD1 has been reported in Arabidopsis and tomato by Morales-Navarro et al [36]. Although SDD1 strongly influences stomatal development, the proteolysis of EPF members by the SDD1 remains elusive [31,39].…”
Section: Subtilisin-like Serine Proteasesmentioning
confidence: 74%
See 1 more Smart Citation
“…Stomatal and pavement cell densities and stomatal indexes were scored in the terminal leaflet of the third leaf of 25-day-old plants. Leaflets were hand-excised, fixed, and clarified as indicated in Morales-Navarro et al (2018) with minor modifications. Plant material was fixed in ethanol:acetic acid 9:1 (v/v) for 48 h, rehydrated through ethanol series, and cleared in a chloral hydrate:glycerol:water solution (8:1:2, w/v/v) for 48 h. The abaxial epidermis was inspected with differential interference contrast (DIC) under a Nikon Eclipse 90i upright microscope and a DXM1200C camera for image acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Although SDD1's mechanism of action is currently unclear (Pillitteri and Dong, 2013), its overexpression reduces stomatal density. Overexpression of ZmSDD1 has been exploited to improve drought resistance in maize (Liu et al, 2015) and recently a wild tomato SDD1-like gene SchSDD1 was shown to improve water deficit tolerance in cultivated tomato (Morales-Navarro et al, 2018). However, it remains unclear how SDD1 overexpression affects seed and fruit development as no harvest or yield data were reported for these species in either studies.…”
Section: Targeting Stomatal Developmentmentioning
confidence: 99%